2011
DOI: 10.1074/mcp.m900641-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Proteome-wide Dysregulation by PRA1 Depletion Delineates a Role of PRA1 in Lipid Transport and Cell Migration

Abstract: We have previously identified prenylated Rab acceptor 1 (PRA1) as a novel cellular interacting partner for EpsteinBarr virus-encoded oncoprotein, latent membrane protein 1 (LMP1). The intracellular trafficking and full signaling of LMP1 requires its interaction with PRA1. To further explore the role of PRA1 in Epstein-Barr virus-associated nasopharyngeal carcinoma (NPC) cells, we generated several PRA1-knockdown cell clones, which exhibited altered cell morphology and increased cell motility. We identified pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 84 publications
3
24
0
Order By: Relevance
“…Of PRA1, about two-thirds was depleted upon NDRG1 silencing. PRA1 has been shown to interact with NDRG1 and regulate several endosomal Rab GTPases, including Rabs 4, 5, 7 and 9 (Bucci et al, 1999;Sivars et al, 2003), and to affect the endosomal cholesterol content (Liu et al, 2011). Moreover, we found that PRA1 overexpression alleviates the LDLR redistribution in NDRG1-silenced cells.…”
Section: Ndrg1 As a Regulator Of Endosomal Morphology And Functionsupporting
confidence: 53%
“…Of PRA1, about two-thirds was depleted upon NDRG1 silencing. PRA1 has been shown to interact with NDRG1 and regulate several endosomal Rab GTPases, including Rabs 4, 5, 7 and 9 (Bucci et al, 1999;Sivars et al, 2003), and to affect the endosomal cholesterol content (Liu et al, 2011). Moreover, we found that PRA1 overexpression alleviates the LDLR redistribution in NDRG1-silenced cells.…”
Section: Ndrg1 As a Regulator Of Endosomal Morphology And Functionsupporting
confidence: 53%
“…Sivars and colleagues [43] proposed a third function of PRA1 as a guanine nucleotide dissociation inhibitor (GDI) displacement factor (GDF) that aids in recycling Rabs during vesicular trafficking. An additional role for PRA1 in lipid transport, modulation of lipid homeostasis, and cell migration has been proposed based on proteomic analysis of PRA1 depleted nasopharyngeal carcinoma cells [44] and further supported by studies implicating PRA1 in the fusion of transport vesicles with the plasma membrane [45]. Finally, evidence supports a role for PRA1 in transport and assembly of viral proteins, although in some cases it may play an inhibitory role [45-49].…”
Section: Discussionmentioning
confidence: 98%
“…The PRA1-LIR intensity in the perinuclear region of the rd1 GCL is also reduced at P21, consistent with a possible role of PRA1 in neurite remodeling and sprouting. Virtually all of the proteins altered in PRA1-depleted nasopharyngeal carcinoma cells that are linked to changes in cell migration [44] are also known to be important in neurite outgrowth. In the inner retina we found similar average intensities of PRA1-LIR at all time points examined except at P8, most likely an anomalous result due to small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…We used a ProteinProphet probability score of Ն 0.90 to ensure an overall false positive rate below 1%, and excluded proteins identified with only a single peptide hit. Protein quantification was achieved with the Libra program (38,39,43), using the default setting. A weighted average of the peptide iTRAQ ratios per protein was used to quantify the protein.…”
Section: Methodsmentioning
confidence: 99%